ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 060886 KOTA MEDAN: Penelitian Kualitatif deskriptif - Raisyah Aulia Nabila Lubis; Hanna Putri Syahkira; Winara; Wildansyah Lubis (STKIP Subang, 2026)
This study aims to analyze the leadership style of the principal in improving teacher performance at SD Negeri 060886 Medan City. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The research subjects consisted of the school principal, a senior teacher in grade I, a young teacher in grade V, and a senior teacher in grade VI. The theories used as the main foundation are transformational leadership theory and democratic leadership theory. The results of the study show that the principal of SD Negeri 060886 Medan City applies a combination of transformational and democratic leadership styles. The transformational leadership style is reflected in the principal's efforts to inspire and motivate teachers through a clear vision, namely realizing a child-friendly, high-achieving, character-based, and digital literacy-based elementary school. Meanwhile, the democratic leadership style is manifested in the involvement of teachers in decision-making through teacher council meetings and joint discussions. Communication built by the principal is open and warm, so as to create a harmonious working relationship. The principal's efforts to improve teacher performance are carried out through appreciation in the form of praise, recognition, and the provision of training opportunities. The constraints faced include differences in the character and adaptability of teachers to technological developments and curriculum changes. Overall, the leadership style applied by the principal has a significant positive impact on teacher discipline, motivation, and work performance.